Neutrophil Chemotaxis in Moving Gradients. Issue 7 (29th May 2018) - Qasaimeh, Mohammad A.; Pyzik, Michal; Astolfi, Mélina; Vidal, Silvia M.; Juncker, David
Abstract: Neutrophils are known to rapidly migrate to sites of infection and injury, and track bacteria guided by spatiotemporally controlled chemokine gradients. Previous studies of neutrophil chemotaxis, using micropipettes and lately microfluidic devices, are limited to stationary sources and gradients. Thus, despite the well‐known ability of neutrophils to track bacteria in vitro, their response to defined moving gradients remains unknown. Here, a "floating" concentration gradient of interleukin‐8 is generated using a microfluidic quadrupole, and neutrophils cultured in a Petri dish are challenged with steep stationary and moving gradients. Individual neutrophils are tracked by live microscopy and their chemotaxis is analyzed. Interestingly, neutrophils are shown to enter the gradient region in a rolling‐like behavior, rapidly adhere to the bare dish, and polarize within 30 s, faster than what has been observed to date. Under stationary gradients, neutrophil migration length is maximal for cells located at the low end of the gradient, whereas under moving gradients, neutrophils migrate over longer distances and the length travelled is independent of their starting position. Furthermore, neutrophils are shown to initiate their migration at a maximum speed, slowing down when migrating deeper into the gradient and eventually stopping. This work lays the foundation for future chemotaxis assays with moving gradients. Abstract : A "floating" concentration gradient of interleukin‐8 is generated using a microfluidic quadrupole, and neutrophils cultured in a Petri dish are challenged with steep stationary and moving gradients. Neutrophil responses, at the single‐cell level, are studied under moving gradients and compared to results from stationary gradients. This study uncovers several fascinating neutrophil behaviors during migration and under moving gradients.